Cone-Beam Computed Tomography (CBCT) Study on Gender Difference and Root Canal Morphology in Mandibular Premolars - Sukriti Paul; Ankita Gupta; Ranu S. Ingole; Yogesh S. Ingole; Seema B. Vaidya; Pranav V. Manek; Sugandha Arya (Wolters Kluwer Medknow Publications, 2024)
Introduction: The study examined mandibular premolars' root and canal distribution across genders and sides. Materials and Methods: Cone-beam computed tomography (CBCT) imaging of mandibular premolars was performed using SINORA ORTHOPHOS XG 3D, with specific parameters set. Results: Cone-beam computed tomography (CBCT) imaging of 100 participants revealed mostly single-rooted premolars, with slight variations, notably among females. Mandibular first premolars predominantly had single canals and roots, with a higher occurrence of two canals in females. Statistical analysis showed no significant gender- or side-based differences in root distribution. The findings underscore gender-specific variations in premolar morphology, highlighting the importance of tailored treatment planning, especially for the left side. Conclusion: While CBCT proves valuable, further research is needed to optimize its utility in endodontic decision-making.